A facile approach for grafting ion imprinted polymer onto magnetic multi-walled carbon nanotubes for selective removal and preconcentration of cadmium in food and wastewater samples prior to atomic spectrometric determination. (30th March 2023) - Islam, Aminul; Rais, Saman
Graphical abstract: Highlights: New MWCNT based magnetic IIP synthesized for SPE coupled FAAS method development. Serves twin objective of determination and removal in food, water, wastewater. Analytical method validation; SRM, recovery, accuracy, precision, robustness. Cd(II) loaded IIP was exploited for removal of toxic anionic dyes. Abstract: A 3D Fe3 O4 @MWCNT-CdIIP was synthesized by the oxidizing surface of multi-walled carbon nanotubes with carboxylic acid end groups and its subsequent termination with an ion imprinted polymer. An artificial neural network manifests better predictability than the central composite design methodology for optimising the adsorption procedure. The adsorption capacity was 109 mg g −1 (2.5 times more than non-imprinted polymer) under optimized conditions (pH; 5.6, time; 15 min, concentration; 800 μg mL −1 temperature; 25 °C), which was in accord with Toth isotherm. Fractal-like pseudo-second-order kinetics was found reasonably fast, with 66 % adsorption in 5 min. Solid phase extraction coupled Flame atomic absorption spectrometry method provides selective recognition towards Cd(II), with limit of detection; 1.13 µg/L, limit of quantification; 3.21 µg/L after preconcentration (preconcentration factor; 50) and good robustness. The developed method was applied for Cd(II) determination in food (tea, coffee, bread, tobacco, radish, spinach), water and wastewater (>99 % removal as well). Cd(II) loaded IIP was further utilized to remove anionic dyes with >95 % removal.